LITERATURE REVIEW ON FACTORS INFLUENCING THE IMPLEMENTATION OF HOSPITAL INFORMATION MANAGEMENT SYSTEMS - Johan, Herni; Dzakwan, Muhammad Sabiq; Ramlah; arianto, yogi; Mirojialtim, Anugerah (Proceeding of International Conference on Multidisciplinary Research, 2024)
Today the development and progress of information technology is growing rapidly. Application systems in various fields are a must for an agency / company to utilize information as a basis for administration and data processing (Deddy, 2016). The implementation of an information system in hospitals (SIMRS) is very important to achieve quality services. However, it is necessary to monitor and evaluate to find out how the benefits of SIMRS in the hospital work unit. Thus, it allows the hospital to develop SIMRS taking into account the factors that influence and benefit the use of SIMRS. The purpose of this literature review is to determine the driving and inhibiting factors in the implementation of Information Management Information Systems. The method used is the electronic data base method, the search for journals using google school with the keyword "management information systems in hospitals", totaling 20,600 journals but only using 5 journals that match the criteria. The results of the study identified three main root causes, namely the completeness of standard operational procedures (SOP) and management, human resource capabilities, systems and technology.